2016
DOI: 10.1080/10810730.2015.1131777
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Health Literacy Test-30-Spanish (CHLT-30-DKspa), a New Spanish-Language Version of the Cancer Health Literacy Test (CHLT-30) for Spanish-Speaking Latinos

Abstract: Objective Describe adaptation and initial validation of the Cancer Health Literacy Test (CHLT) for Spanish-speakers. Methods Cross-sectional field test of the CHLT Spanish version (CHLT-30-DKspa) among healthy Latinos in Louisiana. Diagonally Weighted Least Squares were used to confirm the factor structure. Item-Response Analysis using 2-parameter logistic estimates were used to identify questions that may require modification to avoid bias. Cronbach's alpha coefficients estimated scale internal consistency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…To our knowledge, only few studies had demonstrated an association between HL and QOL among cancer survivors in China using three brief screening questions. Previous research has used more complex and extensive questionnaires to measure HL, such as the Rapid Estimate of Adult Literacy in Medicine,22 30 Cancer Health Literacy Test-30,31 Short-Form Test of Functional Health Literacy in Adults5 32 33 and others, which are impractical for use in busy clinical settings. Despite differences in the nature of HL assessment techniques, our results are consistent with those of previous studies that identified inadequate HL as a risk factor for QOL among cancer survivors 5 14 34.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only few studies had demonstrated an association between HL and QOL among cancer survivors in China using three brief screening questions. Previous research has used more complex and extensive questionnaires to measure HL, such as the Rapid Estimate of Adult Literacy in Medicine,22 30 Cancer Health Literacy Test-30,31 Short-Form Test of Functional Health Literacy in Adults5 32 33 and others, which are impractical for use in busy clinical settings. Despite differences in the nature of HL assessment techniques, our results are consistent with those of previous studies that identified inadequate HL as a risk factor for QOL among cancer survivors 5 14 34.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 depicts our conceptual framework for this study. CHL implies having the skills and competencies required to seek and understand cancer-related information and risks and make decisions about cancer diagnosis, treatments, and participation in research [ 17 ]. As individuals acquire health-related information, they make informed decisions regarding cancer care and participation, ultimately reducing their health risks and improving their quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…Spanish (CHLT-30-DKspa) and English (CHLT-30-DKeng) versions of the CHLT-30 (Cronbach Alpha = 0.88) were used. Because the Spanish version included a “don’t know” (DK) response option for each question [ 17 ], we added the same DK response option to the English version and pilot-tested it among 24 English-speaking members of the African American and White communities (12 in each community). The CHLT-30 includes 30 multiple-choice questions related to different domains of cancer health literacy (knowledge, reading, and numeracy), where only one response option is correct for each item.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on widely accepted definitions of HL [2,3], Echeverri and colleagues defined Cancer Health Literacy (CHL) as the “individual’s capacity to seek out, comprehend, evaluate, and use basic information and services needed to make appropriate decisions regarding cancer prevention, diagnosis and treatment” [10, p70]. Only a few CHL measures were available in Spanish at the time we conducted this study: the Cancer Literacy Measure [11], the Cultural Cancer Screening Scale [12]; and the Cervical Cancer Literacy Assessment Tool [13].…”
Section: Introductionmentioning
confidence: 99%